2022
DOI: 10.18048/2022.62.03
|View full text |Cite
|
Sign up to set email alerts
|

Natural Refrigerant on Board Marine Vessels

Abstract: The paper deals with the topic of refrigerants, their historical evolution, applied legislation and trends in maritime affairs. Regarding the Environmental care paper considers the impact of refrigerants of refrigeration systems, both on stationary plants on land and on plants on board. New regulations of the European Union, and IMO maritime organization, require the reduction and complete abolition of harmful synthetic refrigerants and the introduction of new refrigerants that will have a significant economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Annual total cost approach was used for cost analysis. In the calculations, using Equations (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), the total costs of R22 and R134a gases are calculated as $86875 and $94488, respectively. The effects of the use of alternative refrigerants on the total cost of the system are shown in Table 6 separately for to R22 and R134a.…”
Section: Economical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual total cost approach was used for cost analysis. In the calculations, using Equations (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), the total costs of R22 and R134a gases are calculated as $86875 and $94488, respectively. The effects of the use of alternative refrigerants on the total cost of the system are shown in Table 6 separately for to R22 and R134a.…”
Section: Economical Resultsmentioning
confidence: 99%
“…Ammar and Seddiek (2018) pointed out that 8.0% of the global CO 2 emissions are from ships which is shown in R22 and R134a refrigerants usage is dominating the refrigeration preference in maritime sector. The world merchant fleet's total HCFCs/HFCs usage percentages are estimated as 70% for R22, 26% for R134a, and 4% for R404A (Glavan at al., 2022). The production and supply of R22 and R404A is prohibited by 2020 and the use of R134a in new systems is prohibited by 2024.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low GWP working fluids of which the utmost GWP limit was defined as 2500 GWP, have to be used onboard EU-flagged ships after 1 January 2020. 24 Considering the thermo-economic parameters and legislation, six working fluids from hydrocarbons (HC), hydrofluorocarbons (HFC) and hydrofluoroolefins (HFO) are analyzed in this study as shown in Table 2. In this table, H, I and F denote Health, Instability and Flammability, respectively.…”
Section: Orc Whr Systemmentioning
confidence: 99%